Modernismo, pasado-presente. El México de Saturnino Herrán (Tzintzun, Revista de Estudios Históricos, 2016)
Mexican modernism is a movement that provides important insights both tothe history of the Mexican aesthetics, as well as to the relection and to theconstruction of the image of what is “Mexican”. he reassessment of Mexicanmodernism enables veriication that the revolutionary period does not necessarilyrepresent, much less as it was intended, a rupture in the constructionof a narrative and of a national identity with respect to the immediately precedingperiod. Issues such as indigenism, miscegenation and the very idea ofnation are developed even more in the Poririate. However, modernism is alsoan original and peculiar movement, and given that its relation to the image isless sacralized and freer than in previous and subsequent periods. his allowsit to acquire two rare traits, particularly in painters like Julio Ruelas and SaturninoHerrán: irst of all, a great opening and reception of international artand to its diversity of styles; and secondly, an equally desacralized and nonideologicaldialogue between the diverse arts and eras.
Keywords: Mexican modernism; Julio Ruelas; Saturnino Herrán; poririate; National identity